Isolating membrane, battery monomer, battery and electric device
Patent Information
- Application Number
- CN202380060957.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-04-17
AI Technical Summary
The storage performance of existing battery cells is poor and needs to be improved.
An isolation membrane is used, which includes an isolation body and an aldehyde-ketone polymer layer disposed on the surface of the isolation body. The aldehyde-ketone polymer molecular chain is flexible and can diffuse in the electrolyte and build a three-dimensional network interface to improve the concentration of active ions. The diffusion rate and conductivity reduce concentration polarization, allowing active ions to embed into the pole piece quickly and evenly.
Significantly improves the storage performance of battery cells. By reducing the entangled state of molecular chains and the risk of polymer dissolution, it enhances the mutual attraction between the polymer and the electrolyte, forming a gel-like structure to lock the electrolyte, and improves the transmission of lithium ions. rate and overall performance stability of the battery.
Smart Images

Figure CN119790539A_ABST
Abstract
Description
Separator, battery cell, battery and electrical device Technical Field
[0001] The present application relates to the field of batteries, and in particular to an isolation membrane, a battery cell, a battery, and an electrical device. Background Art
[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.
[0003] As battery applications become increasingly widespread, the performance requirements for battery cells are becoming increasingly stringent. However, the current storage performance of battery cells is relatively poor and still needs to be further improved.
[0004] Summary of the Invention
[0005] The embodiments of the present application are made in view of the above-mentioned problems, and an object thereof is to provide a separator, a battery cell, a battery, and an electric device.
[0006] The first aspect of the present application provides an isolation membrane, the isolation membrane comprising an isolation body and a polymer layer provided on at least one surface of the isolation body, the polymer layer comprising an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is formed on (T m The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency sweep test at +20) °C. The slope of the elastic modulus G'-energy loss modulus G" curve is K, 0.8≤K<∞, T m °C represents the melting temperature of the aldehyde-ketone polymer.
[0007] Therefore, when the polymer of the embodiment of the present application meets the above range, the entanglement state of the molecular chains can be reduced, which is beneficial to the diffusion of the electrolyte between the molecular chains; and the polymer still maintains a certain molecular chain entanglement state, which can lock the electrolyte inside the polymer, and can reduce the risk of the polymer dissolving in the electrolyte, thereby improving the stability of the polymer performance; the polymer and the electrolyte can construct a three-dimensional connected interface between the isolation membrane and the electrode, and the interface has a network structure, which is beneficial to increase the rate of diffusion of active ions such as lithium ions from the electrolyte phase to the electrode, and increase the conductivity of the isolation membrane, reduce concentration polarization, and allow the active ions to be quickly embedded in the electrode and evenly deposited, thereby improving the storage performance of the battery cell.
[0008] In some embodiments, 0.8≤K≤100; optionally, 0.8≤K≤10.
[0009] In some embodiments, an aldehyde-ketone polymer is added to a first solvent at 70°C to form an aldehyde-ketone polymer system; the aldehyde-ketone polymer system is allowed to stand for 8 hours at 70°C and for ≥24 hours at 25°C, and then the aldehyde-ketone polymer system is filtered through a 200-mesh filter to leave a first substance, wherein the mass of the aldehyde-ketone polymer is q, and its unit is g; the mass of the first substance is m, and its unit is g; the aldehyde-ketone polymer and the first substance satisfy: 5≤m / q≤1000. The embodiments of the present application can achieve the stretching of the polymer molecular chain within the safe operating temperature range of the battery cell by increasing the temperature, and promote the mutual attraction and physical combination of the polymer molecular chain and the electrolyte. At room temperature, the activity of the aldehyde-ketone polymer molecular chain segments is reduced, and they remain attached to the surface of the isolation body and lock the electrolyte in the spatial environment where the polymer is located, forming a gel or a gel-like state, which can increase the transmission rate of active ions such as lithium ions and improve storage performance.
[0010] In some embodiments, the aldehyde-ketone polymer has a glass transition temperature (Tg) in °C, where -100 ≤ Tg ≤ 50; alternatively, -80 ≤ Tg ≤ 30. A polymer with a relatively low glass transition temperature has greater molecular chain segment flexibility, making it easier for adjacent molecular chains to be opened.
[0011] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (I),
[0012] In formula (I), R1 includes a single bond, a substituted or unsubstituted C1-C6 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group; alternatively, R1 includes a single bond, a substituted or unsubstituted C1-C4 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.
[0013] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-6),
[0014] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (II),
[0015] In formula (II), R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.
[0016] Alternatively, R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.
[0017] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-4),
[0018] In some embodiments, n is a positive integer selected from 500 to 15,000.
[0019] In some embodiments, the molecular weight of the aldehyde-ketone polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0020] When the molecular weight of the aldehyde-ketone polymer is within the above range, the molecular chains of the aldehyde-ketone polymer can be stretched in the electrolyte, but are not easily completely dissolved and dispersed by the electrolyte, which is beneficial to regulating the uniform distribution and dispersion of the aldehyde-ketone polymer molecular chains in the electrolyte; and can further improve the flexibility between the molecular chains of the aldehyde-ketone polymer, and the interaction force between the molecular chains is relatively weak, which is beneficial for the solvent molecules in the electrolyte to open the molecular chains and enter between the molecular chains and be wrapped by the molecular chains, thereby facilitating the active ions to enter the active substance through the solvent, thereby realizing the smooth and rapid migration of the active ions.
[0021] In some embodiments, the isolation body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.
[0022] In some embodiments, the isolation body includes a substrate and a heat-resistant coating, the heat-resistant coating is disposed on at least one surface of the substrate, and the polymer layer is disposed on a surface of the heat-resistant coating facing away from the substrate.
[0023] In some embodiments, the polymer layer further comprises heat-resistant particles. The heat-resistant particles and the aldehyde-ketone polymer act synergistically to further enhance the heat resistance and ion transmission performance of the separator as a whole.
[0024] In some embodiments, based on the total mass of the polymer layer, the ratio of the mass percentage of the aldehyde-ketone polymer to the mass percentage of the heat-resistant particles is (0.2 to 5):1, or optionally (0.5 to 2):1. When the contents of the heat-resistant particles and the aldehyde-ketone polymer are within the above ranges, the heat resistance and ion transport properties of the separator can be further improved.
[0025] In some embodiments, the coating weight of the polymer layer can be 0.5 mg / 1540.25 mm2 Up to 5mg / 1540.25mm 2 When the coating weight of the polymer layer is within the above range, the heat resistance and ion transmission performance of the separator as a whole can be further improved.
[0026] In a second aspect, the present application proposes a battery cell comprising an isolation membrane as described in any embodiment of the first aspect of the present application.
[0027] In a third aspect, the present application proposes a battery comprising a battery cell as described in any embodiment of the second aspect of the present application.
[0028] In a fourth aspect, the present application proposes an electrical device comprising a battery as described in any embodiment of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0030] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.
[0031] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .
[0032] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.
[0033] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.
[0034] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0035] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0036] The drawings are not necessarily drawn to scale.
[0037] The following are the descriptions of the reference numerals:
[0038] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0039] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0040] 53. Cover plate;
[0041] 6. Electrical equipment. DETAILED DESCRIPTION
[0042] The following detailed description specifically discloses the embodiments of the separator, battery cell, battery, and electrical device of the present application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0043] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0046] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.
[0047] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0048] In this application, the terms "plurality" and "multiple" refer to two or more.
[0049] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.
[0050] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.
[0051] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.
[0052] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0053] A battery cell includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet to isolate the positive electrode sheet from the negative electrode sheet. There is a solid-liquid contact interface between the electrode sheet and the electrolyte, and side reactions may occur at this contact interface, deteriorating the performance of the battery cell. Taking the positive electrode sheet as an example, there is a solid-liquid contact interface between the positive active material contained in the positive electrode sheet and the electrolyte. At this interface, the positive active material may undergo side reactions with the electrolyte, deteriorating the storage performance of the battery cell, and the side reactions may produce products that are not conducive to the cycle of the battery cell, thereby deteriorating the storage performance of the battery cell.
[0054] In view of the above problems, the embodiment of the present application proposes an isolation membrane from the perspective of constructing an interface. The isolation membrane includes an isolation body and a polymer layer arranged on at least one surface of the isolation body. The polymer molecular chains in the polymer layer have segment flexibility. When the isolation membrane is applied to a battery cell, the polymer layer contacts the electrolyte, the polymer molecular chains stretch and open, and the electrolyte can diffuse between the molecular chains, forming a three-dimensional connected interface between the isolation membrane and the electrode. The interface has a network structure, which is conducive to increasing the rate of diffusion of active ions such as lithium ions from the electrolyte phase to the electrode, and increasing the conductivity of the isolation membrane, reducing concentration polarization, so that the active ions are quickly embedded in the electrode and evenly deposited, thereby improving the storage performance of the battery cell.
[0055] Isolation film
[0056] In a first aspect, an embodiment of the present application provides an isolation membrane, comprising an isolation body and a polymer layer disposed on at least one surface of the isolation body, wherein the polymer layer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is formed in (T m The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency sweep test at +20) °C. The slope of the elastic modulus G'-energy loss modulus G" curve is K, 0.8≤K<∞, T m °C represents the melting temperature of the aldehyde-ketone polymer.
[0057] Specifically, the preparation process of the sheet structure is as follows: the polymer is vacuum dried at 80°C for 12 hours. The dried polymer is hot-pressed into a thin sheet by a flat vulcanizer, the hot pressing temperature is set to (Tm+20)°C, the calendering thickness is 1-2min, the calendering time is 2min, and the pressure is 8MPa. After calendering for 2 minutes, the sample is taken out and placed on another vulcanizer of the same model for cold pressing, and the cold pressing pressure is 10MPa. A fixed 10-size polymer disc (sheet structure) can be obtained using a circular mold with a diameter of 25mm. For example, the sheet structure can be a disc with a thickness of 1-2mm and a diameter of 25mm; it can also be prepared according to the sample standards required by the test equipment.
[0058] According to the conclusions of classical linear viscoelasticity, for polymers, the elastic modulus G'-dissipation modulus G" in the terminal region of the elastic modulus G'-dissipation modulus G" curve (the interval approaching the maximum angular velocity) conforms to the frequency dependence, and the longest chain of the polymer plays a role in the viscoelastic behavior.
[0059] The dynamic frequency sweep test was performed using a TA-AR2000EX rotational rheometer (TAinstruments, USA). The parallel plate had a diameter of 25 mm and a thickness of 0.9 mm. To ensure the test was conducted within the linear tapping region, the strain was 2%, the test temperature was Tm + 20°C, and the frequency sweep range was 500 rad / s ≤ w. 2 ≤0.05rad / s, so as to obtain data in the lowest possible frequency range.
[0060] The dynamic frequency sweep test can characterize the degree of entanglement of molecular chains under solid phase melting (melt state). Compared with linear structures or short branched structures, long branched structures, network structures and low cross-linked structures have a high degree of entanglement, which will show deviation from linear terminal behavior, and the polymer will show solid phase behavior. When the polymer of the present application meets the above range, the entanglement state of the molecular chain can be further reduced, which is beneficial to the diffusion of the electrolyte between the molecular chains; and the polymer still maintains a certain molecular chain entanglement state, which can lock the electrolyte inside the polymer and reduce the risk of the polymer dissolving in the electrolyte, thereby improving the stability of the polymer performance; the polymer and the electrolyte can form a three-dimensional connected interface between the isolation membrane and the electrode, and the interface has a network structure, which is beneficial to increase the rate of diffusion of active ions such as lithium ions from the electrolyte phase to the electrode, and improve the conductivity of the isolation membrane, reduce concentration polarization, and enable the active ions to be quickly embedded in the electrode and uniformly deposited, thereby improving the storage performance of the battery cell.
[0061] In some embodiments, 0.8≤K≤100; optionally, 0.8≤K≤10.
[0062] Illustratively, K may be 0.8, 1, 1.01, 1.1, 1.2, 1.5, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the foregoing values.
[0063] In some embodiments, the glass transition temperature of the aldehyde-ketone polymer is Tg, which is expressed in °C, and is -100≤Tg≤50; optionally, -80≤Tg≤30.
[0064] The glass transition temperature is the temperature at which polymer chain segments transition from frozen to moving. The glass transition temperature has a certain impact on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature. The higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured using differential scanning calorimetry (DSC). Specifically, the test steps are as follows: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and heat and cool the sample in a nitrogen atmosphere. The sample is heated at a rate of 10℃ / min from an initial temperature 20℃ lower than the intrinsic Tg of the material to a cutoff temperature 20℃ higher than the intrinsic Tm of the material. The actual glass transition temperature (Tg) and melting temperature (Tm) of the material are determined based on the endothermic and exothermic peaks or transition points of the material during the process.
[0065] The glass transition temperature of the polymer is relatively low, the molecular chain segments are more flexible, and adjacent molecular chains are more easily opened. For example, the glass transition temperature of the aldehyde-ketone polymer can be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0066] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (I),
[0067] In formula (I), R1 includes a single bond, a substituted or unsubstituted C1-C6 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group;
[0068] Alternatively, R1 includes a single bond, a substituted or unsubstituted C1-C4 methylene group.
[0069] Alternatively, R1 includes a single bond, a substituted or unsubstituted C1-C2 methylene group.
[0070] Alternatively, R2 includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.
[0071] In the embodiments of the present application, a single bond indicates that the group does not exist, and the atoms on both sides of the group are connected by a single bond. For example, R1 is a single bond, which indicates that the carbon atoms on both sides of R1 are connected in the form of a single bond.
[0072] Illustratively, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-6),
[0073] Exemplarily, the aldehyde-ketone polymer includes a structural unit represented by formula (II),
[0074] In formula (II), R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.
[0075] Alternatively, R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.
[0076] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-4),
[0077] The molecular chain entanglement degree of the above-mentioned aldehyde-ketone polymer is low, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby further improving the interface performance.
[0078] The above-mentioned polymers are only examples of the structural groups of the main molecular chains. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).
[0079] The groups of the polymers of the present application can be detected by infrared spectrophotometry IR. Specifically, the polymers are tested using a Thermo Nicolet Nexus 670 attenuated total reflection Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.
[0080] The structure of the polymer of the present application can be tested by nuclear magnetic resonance NMR. Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.
[0081] The polymer monomer type of the present application (especially suitable for monomers with a smaller proportion in the polymer) can be tested by pyrolysis-gas chromatography-mass spectrometry. The specific test steps are as follows: accurately weigh 0.5 mg of sample and put it into the sample cup. After fixing it to the injection rod, it is loaded into the pyrolyzer installed near the GC (gas chromatography) inlet. After the pyrolyzer temperature reaches the set temperature, press the injection button, and the sample cup falls rapidly into the core of the pyrolysis furnace by free fall. In the inert gas N2 atmosphere, the volatile components are instantly vaporized and carried into the gas chromatography column by the carrier gas for separation. Finally, it is detected by the flame ionization detector FID or the mass spectrometer MS to obtain a gas chromatogram or a total ion current diagram.
[0082] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, a carboxyl group, an amide group, a carboxyl group, an ester group, and a halogen atom such as a chlorine atom, a fluorine atom, or a bromine atom. These substituents are high-pressure-resistant substituents and are more conducive to stabilizing the polymer structure.
[0083] In some embodiments, n is a positive integer selected from 500 to 15,000.
[0084] Optionally, n is selected from a positive integer between 500 and 10,000.
[0085] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0086] When the molecular weight of the aldehyde-ketone polymer is within the above range, the molecular chains of the aldehyde-ketone polymer can be stretched in the electrolyte, but it is not easy to be completely dissolved and dispersed by the electrolyte, which is conducive to regulating the uniform distribution and dispersion of the aldehyde-ketone polymer molecular chains in the electrolyte; and it can further improve the flexibility between the molecular chains of the aldehyde-ketone polymer. The interaction force between the molecular chains is relatively weak, which is conducive to the solvent molecules in the electrolyte opening the molecular chains and entering between the molecular chains and being wrapped by the molecular chains. This is conducive to the active ions entering the active material through the solvent, realizing the smooth and rapid migration of the active ions. For example, the molecular weight of the aldehyde-ketone polymer can be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol or a range consisting of any two of the above values.
[0087] The molecular weight of a polymer is well known in the art and can be measured using equipment and methods commonly used in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously perform an external ultraviolet (53 KHz / 120 W) for 5 minutes to ensure that the sample is completely dispersed. Then, the sample is measured in accordance with GB / T19077-2016 / ISO13320:2009 standard.
[0088] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC instrument (Wyatt Technology Corporation, USA) was used in conjunction with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a ViscoStar II viscometer. The test was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.
[0089] When the polymer in the embodiment of the present application further satisfies one or more of the following conditions, the cycle performance and storage performance of the battery cell can be further improved.
[0090] In some embodiments, an aldehyde-ketone polymer is added to a first solvent at 70°C to form an aldehyde-ketone polymer system. The aldehyde-ketone polymer system is then allowed to stand at 70°C for 8 hours and then at 25°C for ≥24 hours. After undergoing these two stages of standing, the aldehyde-ketone polymer system partially swells and adsorbs to form a gel-like substance. The aldehyde-ketone polymer system is then filtered through a 200-mesh filter, leaving the first substance. The mass of the aldehyde-ketone polymer is q, expressed in g; the mass of the first substance is m, expressed in g. The aldehyde-ketone polymer and the first substance satisfy the following conditions: 5 ≤ m / q ≤ 1000; alternatively, 10 ≤ m / q ≤ 1000; further alternatively, 10 ≤ m / q ≤ 50. For example, m / q can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of these values.
[0091] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the polymer to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.
[0092] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include at least one of a carbonate solvent and an ether solvent. For example, the carbonate solvent includes a cyclic carbonate solvent and / or a linear carbonate solvent.
[0093] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.
[0094] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.
[0095] As examples of the ether solvent, the ether solvent includes one or more of tetrahydrofuran THF, 2-methyltetrahydrofuran 2me-thf, 1,3-dioxolane DOL, dimethoxymethane DMM, 1,2-dimethoxyethane DME, and diglyme DG.
[0096] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.
[0097] In this application, m / q is also referred to as the precipitation value, which characterizes the ability of the polymer and the electrolyte to transform into a gel-state substance.
[0098] The first substance mainly includes a gel-state substance formed by a polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer basically does not change.
[0099] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry IR or nuclear magnetic resonance NMR testing shows that the main component of the first substance after drying is the polymer described above.
[0100] By increasing the temperature, embodiments of the present application can achieve stretching of the polymer molecular chains within the safe operating temperature range of the battery cells, promoting mutual attraction and physical bonding between the polymer molecular chains and the electrolyte. At room temperature, the activity of the aldehyde and ketone polymer molecular segments decreases, allowing them to remain attached to the surface of the isolation body and lock the electrolyte within the polymer's spatial environment, forming a gel or gel-like state. This can increase the transmission rate of active ions, such as lithium ions, and improve cycling and storage performance.
[0101] In an embodiment of the present application, the isolation membrane includes an isolation body and a polymer layer, wherein the polymer layer is disposed on at least one surface of the isolation body, meaning that the polymer layer can be disposed on one surface of the isolation body or on both surfaces of the isolation body. Since the isolation body has a variety of structural forms, the polymer layer can accordingly have a variety of configurations. The aldehyde-ketone polymer can be dispersed in a solvent to form a polymer mixture system, and the polymer mixture system is coated on the isolation body via a coating process such as atomization spraying or gravure coating.
[0102] In some embodiments, the isolation body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.
[0103] In other embodiments, the isolation body includes a substrate and a heat-resistant coating, wherein the heat-resistant coating is disposed on at least one surface of the substrate, and the polymer layer is disposed on the surface of the heat-resistant coating facing away from the substrate. It will be understood that the heat-resistant coating can be disposed on one surface of the substrate, or on both surfaces of the substrate.
[0104] The embodiments of the present application are not particularly limited to the material of the substrate. Any known substrate with good chemical and mechanical stability can be selected. For example, the substrate may include at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The substrate may be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer may be the same or different.
[0105] In some embodiments, the porosity of the substrate is greater than or equal to 25%, and can be optionally between 25% and 50%. When the porosity of the substrate is within the above range, the air permeability of the substrate can be improved, which is beneficial for the migration of active ions. Moreover, due to the relatively small porosity, the mechanical properties of the substrate can be improved, and it can provide good support for the polymer layer.
[0106] In some embodiments, the thickness of the substrate may be less than or equal to 16 μm, and may be 5 μm to 12 μm. For example, the thickness of the substrate may be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the above values.
[0107] The heat-resistant coating may include heat-resistant particles. In some embodiments, the heat-resistant particles include at least one of inorganic particles and organic particles. By adding heat-resistant particles, the heat resistance of the isolation film can be improved.
[0108] In some embodiments, the mass percentage of the inorganic particles in the heat-resistant coating is ≤ 30. For example, the mass percentage of the inorganic particles in the heat-resistant coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, or a range consisting of any two of the above values.
[0109] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.
[0110] In some embodiments, inorganic particles having a dielectric constant of 5 or higher may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 ) at least one of O3-PbTiO3 (abbreviated as PMN-PT).
[0111] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass-like (0<x<4, 0<y<13), lithium lanthanum titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w, 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).
[0112] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates with olivine structures, carbon-based materials, silicon-based materials, tin-based materials, and lithium titanium compounds.
[0113] In some embodiments, the heat-resistant coating may also include other organic particles, for example, the organic particles may include polystyrene, polyethylene, polyimide, melamine resin, phenolic resin, polypropylene, polyester (such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyphenylene sulfide, polyaramid, polyamideimide, polyimide, copolymer of butyl acrylate and ethyl methacrylate and mixtures thereof.
[0114] In some embodiments, the heat-resistant coating may further include a binder. For example, the binder may include at least one of an aqueous solution-based acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, or sodium acrylate monomers, or a copolymer with other comonomers), polyvinyl alcohol (PVA), an isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0115] In some embodiments, the thickness of the heat-resistant coating may be ≤4 μm. This helps to improve the energy density of the battery cell. In the embodiments of the present application, the thickness of the heat-resistant coating refers to the thickness of the heat-resistant coating located on a single side of the substrate. For example, the thickness of the heat-resistant coating may be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.
[0116] In some embodiments, the polymer layer may also include heat-resistant particles. The heat-resistant particles and the aldehyde-ketone polymer work synergistically to further enhance the overall heat resistance and ion transport properties of the isolation membrane. The aldehyde-ketone polymer and heat-resistant particles can be dispersed in a solvent to form a polymer mixture system, which is then applied to the isolation body via a coating process such as atomization spraying or gravure coating.
[0117] In some embodiments, based on the total mass of the polymer layer, the ratio of the mass percentage of the aldehyde-ketone polymer to the mass percentage of the heat-resistant particles is (0.2 to 5.0):1, or optionally (0.5 to 2.0):1. When the contents of the heat-resistant particles and the aldehyde-ketone polymer are within the above ranges, the heat resistance and ion transport properties of the separator can be further improved. Illustratively, the ratio of the mass percentage of the aldehyde-ketone polymer to the mass percentage of the heat-resistant particles can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 1.0:1, 1.2:1, 1.5:1, 1.8:1, 2.0:1, 2.5:1, 2.8:1, 3.0:1, 3.2:1, 3.5:1, 3.8:1, 4.0:1, 4.2:1, 4.5:1, 4.8:1, 5.0:1 or a range consisting of any two of the above values.
[0118] In some embodiments, the coating weight of the polymer layer can be 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 When the coating weight of the polymer layer is within the above range, the heat resistance and ion transmission performance of the separator as a whole can be further improved.
[0119] Optionally, the coating weight of the polymer layer can be 0.5 mg / 1540.25 mm 2 Up to 3.5mg / 1540.25mm 2 .
[0120] For example, the coating weight of the polymer layer can be 0.5 mg / 1540.25 mm 2 、0.6mg / 1540.25mm 2 、0.8mg / 1540.25mm 2 、1.0mg / 1540.25mm 2 、1.2mg / 1540.25mm 2 、1.5mg / 1540.25mm 2 、1.8mg / 1540.25mm 2 , 2.0mg / 1540.25mm 2 , 2.5mg / 1540.25mm 2 、3mg / 1540.25mm 2 、3.5mg / 1540.25mm 2 、4mg / 1540.25mm 2 4.5mg / 1540.25mm 2 、5mg / 1540.25mm 2Or a range consisting of any two of the above values.
[0121] In the embodiment of the present application, the coating weight of the polymer layer refers to the single-sided weight. For example, if the polymer layer is provided on both sides of the substrate, the coating weight of the polymer layer here refers to the coating weight of the polymer layer on one side of the substrate.
[0122] The coating weight is a well-known meaning in the art and can be tested using equipment and methods known in the art. The same mother roll substrate and isolation film are cut into 1540.25mm 2 The weight of 10 small discs of the isolation film is weighed respectively, and the coating weight of the polymer in the isolation film can be obtained by calculation.
[0123] battery cells
[0124] In the second aspect, an embodiment of the present application proposes a battery cell, which includes an electrode assembly and an electrolyte, the electrode assembly includes a positive electrode sheet, a negative electrode sheet and an isolation membrane, the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the isolation membrane includes an isolation membrane as in any embodiment of the first aspect of the present application.
[0125] [Positive electrode]
[0126] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.
[0127] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.
[0128] The positive electrode active material layer includes a positive electrode active material, which can be a positive electrode active material commonly known in the art for use in battery cells. For example, the positive electrode active material can include at least one of the following materials: a lithium-containing phosphate compound, a lithium-containing transition metal oxide, a sodium-containing phosphate compound, and a sodium-containing transition metal oxide.
[0129] For example, the general formula of the olivine-type phosphate active material (lithium-containing phosphate compound) is: Li x A y Me a M b P 1-c X c Y z, wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0130] For example, lithium transition metal oxides (layered materials such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich layered and rock salt phase layered materials). The general formula of the layered positive active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y includes one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 One or more of O2 (NCM811) and NCA.
[0131] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0132] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.
[0133] In some embodiments, the positive electrode active material layer may also optionally include a positive electrode binder. The present application embodiment has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%. Compared to the crystallinity of the aldehyde-ketone polymer of the embodiment of the present application, the crystallinity of the positive electrode binder is higher. Compared to the melting temperature of the aldehyde-ketone polymer of the embodiment of the present application, the melting temperature of the positive electrode binder is higher.
[0134] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP). Of course, the preparation of the positive electrode sheet is not limited to the above method; the preparation methods described above can also be used.
[0135] [Negative electrode]
[0136] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material.
[0137] Illustratively, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.
[0138] The negative electrode active material can be any negative electrode active material known in the art for use in battery cells. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.
[0139] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode conductive agent. The present embodiments do not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode active material layer.
[0140] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode binder. The present application embodiment does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder based on the total mass of the negative electrode active material layer is ≤5%.
[0141] In some embodiments, the negative electrode active material layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode active material layer.
[0142] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0143] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water. Of course, the preparation of the negative electrode sheet is not limited to the above method; the preparation methods described above may also be used.
[0144] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode plate described herein further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode active material layer.
[0145] [Electrolyte]
[0146] During the charge and discharge process of a battery cell, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and it can be selected according to actual needs.
[0147] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0148] When the battery cell of the present application is a lithium-ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0149] When the battery cell of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0150] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), diethyl sulfone (ESE), tetrahydrofuran THF, 2-methyltetrahydrofuran 2me-thf, 1,3-dioxolane DOL, dimethoxymethane DMM, 1,2-dimethoxyethane DME, and diethylene glycol dimethyl ether DG.
[0151] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0152] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.
[0153] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0154] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the battery cell may be a soft shell, such as a pouch-type soft shell. The soft shell may be made of plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0155] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.
[0156] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 with a square structure as an example.
[0157] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0158] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.
[0159] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.
[0160] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.
[0161] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.
[0162] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0163] Both the battery module 4 and the battery pack can be used as specific examples of batteries in the embodiments of the present application.
[0164] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0165] Electrical devices
[0166] In a third aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules, and battery packs of the present application. The battery cells, battery modules, and battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0167] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.
[0168] Example
[0169] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0170] Example 1 Preparation of lithium-ion battery
[0171] (1) Preparation of positive electrode sheet:
[0172] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0173] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are thoroughly stirred in an appropriate amount of N-methylpyrrolidone (NMP) to create a positive electrode slurry. The mass ratio of NCM622, conductive carbon black, and PVDF in the positive electrode slurry is 97.5:1.4:1. The positive electrode slurry is coated on a current collector aluminum foil and vacuum-dried at 100°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried at 85°C under vacuum for 4 hours to form the positive electrode sheet.
[0174] (2) Preparation of negative electrode sheet:
[0175] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0176] The negative electrode active material (artificial graphite), conductive agent (carbon black), binder (styrene-butadiene rubber (SBR), and thickener (sodium carboxymethyl cellulose (CMC)) were mixed uniformly in a weight ratio of 97.4:2:0.5:2.6 and added to deionized water to form the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. After cold pressing, trimming, cutting, and slitting, the negative electrode sheet was dried at 120°C under vacuum for 12 hours.
[0177] (3) Preparation of electrolyte:
[0178] In an environment with a water content of less than 10ppm, the non-aqueous organic solvents ethylene carbonate EC and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:7 to obtain an electrolyte solvent. Subsequently, the lithium salt LiPF6 and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0179] (4) Preparation of isolation membrane
[0180] 8 μm polyethylene film (PE) was used as the substrate.
[0181] 15g of aldehyde-ketone polymer was dispersed in 100mL of dimethyl carbonate (DMC) solvent to form a mixed system, which was then sprayed onto both surfaces of a polyethylene film to form polymer layers. Water was used as the atomizing solvent, and the weight content of the mixed system was 1%.
[0182] (5) Preparation of lithium-ion batteries:
[0183] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0184] Comparative Example 1
[0185] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the separator in Comparative Example 1 was a polyethylene film (PE) with a thickness of 7 μm.
[0186] Comparative Example 2
[0187] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the material of the aldehyde-ketone polymer of the isolation membrane in Comparative Example 2 was changed.
[0188] Example 2-1
[0189] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the material of the aldehyde-ketone polymer of the isolation membrane of Example 2-1 was changed.
[0190] Example 3-1 to Example 3-5
[0191] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the thickness of the polymer layer of the separator was adjusted in Examples 3-1 to 3-5.
[0192] Example 4-1
[0193] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, Example 4-1 adjusted the position of the polymer layer of the separator. Specifically, the steps of preparing the separator included:
[0194] 7μm polyethylene film (PE) was used as the separator substrate;
[0195] The silicon oxide particles and the binder aqueous solution type polyacrylic acid are uniformly mixed in an appropriate amount of solvent deionized water at a mass ratio of 20:80 to obtain a coating slurry.
[0196] The prepared coating slurry was applied on both surfaces of a PE substrate using a coater to form a heat-resistant coating.
[0197] 15g of aldehyde-ketone polymer was dispersed in 100mL of dimethyl carbonate (DMC) solvent to form a mixed system, which was then atomized and sprayed onto the surface of the heat-resistant coating to form a polymer layer, thereby obtaining a separator. The atomization solvent was water, and the mass content of the mixed system was 1%.
[0198] Example 4-2 to Example 4-6
[0199] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, Examples 4-2 to 4-6 adjusted the composition of the polymer layer of the separator. Specifically, the steps of preparing the separator included:
[0200] 7μm polyethylene film (PE) was used as the separator substrate;
[0201] Silicon oxide particles and 15 g of an aldehyde-ketone polymer were dispersed in 100 mL of dimethyl carbonate (DMC) solvent to form a mixed system. The mixed system was atomized and sprayed onto the surface of the heat-resistant coating to form a polymer layer, thereby obtaining a separator. The mass ratio of the silicon oxide particles to the aldehyde-ketone polymer in Example 4-2 was 1.5:1; the mass ratio of the silicon oxide particles to the aldehyde-ketone polymer in Example 4-3 was 0.5:1; the mass ratio of the silicon oxide particles to the aldehyde-ketone polymer in Example 4-4 was 2:1; the mass ratio of the silicon oxide particles to the aldehyde-ketone polymer in Example 4-5 was 0.2:1; and the mass ratio of the silicon oxide particles to the aldehyde-ketone polymer in Example 4-5 was 0.5:1.
[0202] The data of the examples and comparative examples are shown in Table 1.
[0203] Test section
[0204] 1. Lithium-ion battery capacity retention test
[0205] The lithium-ion batteries prepared in the examples and comparative examples were charged to 4.25V at a constant current of 1 / 3C at room temperature, then charged to a current of 0.05C at a constant voltage of 4.25V, left for 5 minutes, and then discharged to 2.8V at 1 / 3C. The resulting capacity was recorded as the initial capacity C0. Then the battery was adjusted to 97% SOC and transferred to a 60°C environment for storage. Repeat the above steps for the same battery and simultaneously record the discharge capacity Cn of the battery every 30D. The battery capacity retention rate Pn after every 30D is Cn / C0*100%. The five point values of P1, P2...P5 are used as the vertical coordinates and the corresponding storage time is used as the horizontal coordinates to obtain a dot graph of the battery capacity retention rate and the number of storage days. The battery capacity retention rate data in the table are the data measured after 150D of storage under the above test conditions, that is, the value of P5.
[0206] 2. Lithium-ion battery DC impedance test
[0207] The lithium-ion batteries prepared in the examples and comparative examples were charged at 25°C at a constant current of 1 / 3C to 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C. After standing for 5 minutes, the voltage V1 was recorded. The batteries were then discharged at 1 / 3C for 30s, and the voltage V2 was recorded. The internal resistance DCR1 of the battery after the first cycle was obtained by calculating (V2-V1) / 1 / 3C. The batteries were charged at a constant current of 1 / 3C to 4.25V at room temperature, then charged at a constant voltage of 4.25V to a current of 0.05C. After standing for 5 minutes, the batteries were discharged at 1 / 3C to 2.8V. The obtained capacity was recorded as the initial capacity C0. The batteries were then adjusted to 97% SOC and transferred to a 60°C environment for storage. Repeat the above steps for the same battery every 30 days, and record the internal resistance DCRn of the battery for the nth time (n=1, 2, 3...5) at the same time. Use the five point values of DCR1, DCR2, DCR3...DCR5 as the vertical coordinate and the corresponding number of cycles as the horizontal coordinate to obtain a curve graph of the storage days of the battery discharge DCIR.
[0208] The battery internal resistance increase ratio in the table = (DCRn-DCR1) / DCR1*100%. The data in the table are measured after 150D storage under the above test conditions.
[0209] Test results
[0210] The test results are shown in Table 1.
[0211] Table 1
[0212] In Table 1, 70% formaldehyde means that the molar percentage of formaldehyde is 70% based on the total molar amount of formaldehyde and polyvinyl alcohol.
[0213] As shown in Table 1, compared to Comparative Example 1, the addition of the aldehyde-ketone polymer of the present application to the separator in the present embodiment improves the cycling performance and storage performance of the lithium-ion battery. Compared to Comparative Example 2, when the conditions 0.8≤K<∞, especially 0.8≤K≤100, and optionally 0.8≤K≤10, are satisfied, the molecular chain arrangement of the present embodiment tends to be loose, the interaction force between the molecular chains is small, adjacent molecular chains are easily opened, and chain segment motion is achieved through intermolecular internal rotation, forming a highly flexible molecular chain structure, which can more significantly improve the cycling performance and storage performance of the lithium-ion battery.
[0214] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A separation film, comprising: Isolate the body; A polymer layer disposed on at least one surface of the isolation body, the polymer layer comprising an aldehyde-ketone polymer, in, The aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency scanning test at 20 ° C. The slope of the elastic modulus G'-energy loss modulus G" curve is K, 0.8≤K<∞, T m °C represents the melting temperature of the aldehyde-ketone polymer.
2. The isolation film according to claim 1, wherein: 0.8≤K≤100; optionally, 0.8≤K≤10.
3. The isolation film according to claim 1 or 2, wherein: The aldehyde-ketone polymer is added into the first solvent at 70° C. to form an aldehyde-ketone polymer system; The aldehyde-ketone polymer system is allowed to stand at 70° C. for 8 hours and at 25° C. for ≥24 hours, and the aldehyde-ketone polymer system is filtered through a 200-mesh filter to leave the first substance. The mass of the aldehyde-ketone polymer is q, and its unit is g; the mass of the first substance is m, and its unit is g; the aldehyde-ketone polymer and the first substance satisfy: 5≤m / q≤1000.
4. The separator according to any one of claims 1 to 3, wherein: The glass transition temperature of the aldehyde-ketone polymer is Tg, the unit of which is °C, -100≤Tg≤50; optionally, -80≤Tg≤30.
5. The separator according to any one of claims 1 to 4, wherein: The aldehyde-ketone polymer comprises a structural unit shown in formula (I), In formula (I), R1 includes a single bond, a substituted or unsubstituted C1-C6 methylene group; R2 includes a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group; Optionally, R1 includes a single bond, a substituted or unsubstituted C1-C2 methylene group; Alternatively, R2 includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.
6. The isolation film according to claim 5, wherein: The aldehyde-ketone polymer comprises at least one of the structural units represented by formula (I-1) to the structural units represented by formula (I-6), 7. The isolation membrane according to any one of claims 1 to 6, wherein the aldehyde-ketone polymer comprises a structural unit represented by formula (II), In formula (II), R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s each independently are integers selected from 0 to 5, and at least one of r and s is selected from a positive integer; Optionally, R3 to R6 each independently include a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.
8. The isolation membrane according to claim 7, wherein the aldehyde-ketone polymer comprises at least one of the structural units represented by formula (II-1) to the structural units represented by formula (II-4), 9. The separator according to any one of claims 5 to 8, wherein: n is a positive integer selected from 500 to 15000; and / or The molecular weight of the aldehyde-ketone polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
10. The separator according to any one of claims 1 to 9, wherein: The isolation body comprises a substrate, and the polymer layer is disposed on at least one surface of the substrate.
11. The separator according to any one of claims 1 to 9, wherein: The isolation body comprises a substrate and a heat-resistant coating, wherein the heat-resistant coating is arranged on at least one surface of the substrate, and the polymer layer is arranged on the surface of the heat-resistant coating facing away from the substrate.
12. The separator according to any one of claims 1 to 11, wherein: The polymer layer further includes heat-resistant particles; Optionally, based on the total mass of the polymer layer, the ratio of the mass percentage of the aldehyde-ketone polymer to the mass percentage of the heat-resistant particles is (0.2 to 5):1; optionally (0.5 to 2):
1.
13. The separator according to any one of claims 1 to 12, wherein: The coating weight of the polymer layer is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 . 14 . A battery cell comprising the separator according to claim 1 .
15. A battery comprising the battery cell according to any one of claims 1 to 14.
16. An electrical device comprising the battery according to claim 15.
Citation Information
Patent Citations
Water-soluble organic couple redox flow battery
CN102035007A
Secondary battery separator and secondary battery
CN110663123A
Organic flow battery adopting molecular sieve diaphragm
CN113823822A
Photoelectrocatalysis device and application thereof
CN114405437A
Polyketone paper and separator comprising the same
KR1020180085412A